2019
DOI: 10.4236/fns.2019.102016
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Antioxidative and Anti-Diabetic Potential of Thermally Treated Garlic, Turmeric, and Ginger

Abstract: Spices have been used for centuries for food preservation, flavors, and medicinal properties. Research suggests that garlic, turmeric, and ginger contain potent antioxidants that may prevent and/or delay chronic diseases such as cancer, diabetes, and heart disease. Heat treatment of spices may potentially increase antioxidative activity by modifying the inherent chemical structure of potent antioxidative compounds within spices. The purpose of this study was to determine the impact of thermal treatment of garl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In the case of the ginger rhizome, the highest TPC value (9.63 ± 0.05 mg GA g −1 DW) was found in the methanolic extract, while water resulted in the lowest TPC content (6.42 ± 0.33 mg GA g −1 DW). Similar results were observed in the study by Hester et al [ 70 ].…”
Section: Resultssupporting
confidence: 93%
“…In the case of the ginger rhizome, the highest TPC value (9.63 ± 0.05 mg GA g −1 DW) was found in the methanolic extract, while water resulted in the lowest TPC content (6.42 ± 0.33 mg GA g −1 DW). Similar results were observed in the study by Hester et al [ 70 ].…”
Section: Resultssupporting
confidence: 93%
“…Methanolic extracts derived from ginger samples have demonstrated elevated phenolic content, whereas aqueous extracts obtained from garlic samples have exhibited heightened phenolic content. The occurrence of fat-soluble phenolic compounds, including hydroxybenzoic acid, within methanolic extracts of garlic could potentially contribute to the observed elevation in overall phenolic content [ 36 ]. Thus, total phenolic content serves as a screening parameter for antioxidant activity in plants [ 37 ].…”
Section: Phenolic and Flavonoid Contents In Extractsmentioning
confidence: 99%
“…Other studies have demonstrated heightened oxidation activities in ginger and garlic organic extracts [ 22 , 39 , 40 ]. The heightened presence of phenolic compounds in ginger potentially contributes to its superior antioxidant activity and capacity for scavenging free radicals when compared to garlic [ 36 ]. Furthermore, combination of both exhibited significant increase (85.44%; p < 0.005) in antioxidant activity even at lower concentrations (6 mg/ml) as given in Figure 1 .…”
Section: Antioxidant Activity Of Ginger and Garlic Extractsmentioning
confidence: 99%
“…The improvement in human health protective antioxidant, anti-hyperglycemic, anti-hypertensive, and anti-microbial functional qualities in sprouts and beans following thermal processing might be due to oxidation and polymerization of phenolic bioactives and subsequent modification in their structure-function relationship. Previously, thermally treated (toasted in conventional stove-top) spices (ginger- Zingiber officinale , garlic- Allium sativum , and turmeric- Curcuma longa ) showed high phenolic linked antioxidant and enhanced α-glucosidase enzyme inhibitory activity ( 116 ). In another study, Hester et al ( 115 ) found induced antioxidant activity in Wistar male rat following feeding with thermally treated garlic, ginger, and turmeric.…”
Section: Post-harvest Strategies To Improve Phenolic Bioactive-linked Antioxidant and Anti-diabetic Functionalities Of Plant-derived Foodmentioning
confidence: 99%